2006
DOI: 10.1002/mde.1252
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in the National Basketball Association: a stochastic frontier approach with panel data

Abstract: We investigate how closely NBA teams play up to their potential. We find that shooting, rebounding, stealing the ball and blocking shots raise the number of potential wins while turnovers lower it. We also learn that better coaching and defensive prowess raise a team's win efficiency. Copyright © 2006 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…The modelling of technical inefficiencies was explored by Battese and Coelli (1995). Studies from professional sports that follow this two-stage approach include Dawson et al (2000a,b), Kahane (2005) and Hofler and Payne (2006). Assume that u it has a distribution truncated at zero and given by $ Nðm it ; s 2 u Þ: Mean inefficiency can be modelled as a function of specific firm-level influences by…”
Section: Stochastic Frontier Estimationmentioning
confidence: 99%
“…The modelling of technical inefficiencies was explored by Battese and Coelli (1995). Studies from professional sports that follow this two-stage approach include Dawson et al (2000a,b), Kahane (2005) and Hofler and Payne (2006). Assume that u it has a distribution truncated at zero and given by $ Nðm it ; s 2 u Þ: Mean inefficiency can be modelled as a function of specific firm-level influences by…”
Section: Stochastic Frontier Estimationmentioning
confidence: 99%
“…On the hand, teams with higher career penalty minutes per game may be indicative of teams that play aggressively which, in turn, may lead to greater performance. In addition to these skater measures, we include a measure of goalie input equal to the weighted value of the career save percentage for each team's 9 Others using this approach in sports research include Berri, Schmidt and Brook (2006), Hofler andPayne (1997, 2006), Zak et al (1979). 10 Two points with regard to the team's lineup.…”
Section: Team Skill Levels and Coachingmentioning
confidence: 99%
“…The authors found considerable variation in the efficiency of baseball managers. Since Porter and Scully's (1982) study, many authors have estimated similar effects in other sports, including Kahane (2005) for the National Hockey League (NHL), Hofler and Payne (2006) for the National Basketball Association (NBA), and most relevant to the current study, Dawson et al (2000a,b), Dawson and Dobson (2002), and Frick and Simmons (2008) for European football.…”
Section: Expectations and Previous Research On Managerial Productivitmentioning
confidence: 81%
“…In addition, Kahn (1993) found that among Major League Baseball managers, those with higher predicted salaries (with the predictions based on past record and experience) had higher winning percentages (relative to the team's previous winning percentage) and improved players' performance (relative to the players' previous performance levels) by more than managers with lower predicted salaries. Similarly, Hofler and Payne (2006) found that NBA coaches with more experience, higher career winning percentages, and more current tenure are more productively efficient than otherwise. And Kahane (2005) found that NHL head coaches with higher career winning percentages or those who played for their current team were able to bring the team closer to the production function frontier than otherwise.…”
Section: Expectations and Previous Research On Managerial Productivitmentioning
confidence: 92%